PERSPEKTIF BEBERAPA IDEOLOGI TENTANG EKONOMI (SEBUAH KAJIAN FILSAFAT EKONOMI) - Rabiatul Adawiah (At-Taradhi Jurnal Studi Ekonomi, 2012)
The two big streams of thought coloring the worlds economy until today are socialismand capitalism. Capitalism demands freedom in weatlh accummulation, competitive politics, freemarket in trade, permissive social interaction and unrestricted government. Socialism has theview that people are brothers and sisters, believes in equal sharing, the abolition of the gapbetween the rich and the poor and a tight control of the pesantry by the socialist party. In itsdevelopment, socialism was then seen as neglecting individual freedom in economic activities.The two ideologies need to be balanced in a meeting point, that is a third straight way of eco-nomic thought whereby the capitalists have to give alms for the living costs of the haves-not. Themeeting point, a third idelogy is Islam that in its economic activities has this balance (evenwichtigheid)between capitalism and socialism. In Islamic economy, etics, logics and aesthetics are clear.